The Efficacy of the Reading, Mind Mapping, and Sharing Learning Model in Boosting Students' Problem-Solving Skills - Ardiansyah, Arief; Akbar, Mukhammad Naafiu (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research is motivated by the fact that there are still many teaching practices by teachers who still apply conventional learning approaches. Therefore, this research wants to test a new learning approach that emphasizes aspects of student involvement in their active cognitive processes by using the Reading, Mind Mapping, and Sharing (RMS) learning model. The main objectives of this study include two things. First, to test the effectiveness of the RMS learning model in improving students' academic performance in the form of problem-solving abilities. Second, to see how much influence the RMS learning model has in enhancing the ability to solve these problems. This study used a quasi-experimental research design on two groups of research subjects. Data analysis was carried out using several statistical techniques, namely the independent sample t-test to test the effectiveness of the RMS learning model on problem-solving abilities and calculating the effect size value to see how much influence the RMS learning model had in influencing the increase in problem-solving skills. This study found two findings: the RMS learning model has proven effective in improving problem-solving skills and has a high influence on improving problem-solving abilities. The RMS Learning Model is a foundational strategy for educators in Islamic Religious Education to boost student cognitive engagement.